THE DEVELOPMENT OF FLAT SHAPE MONOPOLY GAME PROJECT INNOVATION BASED ON PJBL LEARNING MODEL - Rahmi; Bayu Iqbal; Syifa Fadila; Yesika Apriliana; Trimurtini (Education Generation Journal, 2022)
Mathematics learning is a type of learning that requires teachers to be able to act and think creatively and innovatively. For teachers to achieve success in a lesson, a learning innovation is needed that can increase student interest and motivation. This article discusses the innovative form of project-based mathematics learning and produces a monopoly board game with a focus on flat shape material. Activities carried out during learning are students in one group doing a project in the form of a monopoly board game with a flat shape. Then later, the finished monopoly game board will be exchanged with other groups and played together in one group. Several questions in the game will be discussed and answered on the assignment sheet. Writing this article aims to describe the development of abilities and understanding of children in elementary schools on the formula, characteristics, and characteristics of flat shapes through the project of making a monopoly game of flat shapes. The type of research we use is a qualitative research which is a literature study and is presented in the form of a description. The results obtained show that students are very enthusiastic about doing projects and carrying out monopoly flat shapes. It is hoped that the interest that arises in students can increase student interest and motivation to learn. So that learning can be well received by students and learning objectives can be achieved optimally.